PRECOCIOUS PUBERTY AND THE SELF ESTEEM OF PREADOLESCENT GIRLS - Catherine Kawira; Nathan Chiroma; Anne Wambugu (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This article examines the relationship between precocious puberty and the self-esteem of preadolescent girls in public primary schools in Kiambu County, Kenya. This article introduces the two variables precocious puberty and self-esteem, reviews the literature on the relationship between the physical, biological, cognitive, and cultural changes of precocious puberty as they relate to the self-esteem of adolescent girls, discusses the findings of the study, and makes conclusions and recommendations. The sample population was 410 preadolescent girls and 8 class teachers, who were purposively sampled from 12 randomly, selected public primary schools in Kiambu County. Primary data was collected using three instruments; a questionnaire structured interviews and focus group discussions. The instruments were pilot tested on 36, 8-12 years old girls from 3 public primary schools in the study location who were omitted from the actual study. The qualitative data was analysed using the content analysis method, while the quantitative data was analysed using the Statistical Package for Social Sciences (SPSS) version 26. Analysed data was presented using tables and figures. Statistical data indicated that there was a significant relationship (Î²=0.354, p=0.000) between precocious puberty and the self-esteem of pre-adolescent girls. This was confirmed by the responses from both interviews and focus group discussions. Given these findings, the researcher study concluded that earlier pubertal maturation as indicated by breast development before age 8 and the onset of menstruation before age 12 can lead to low self-esteem in preadolescent girls. The article recommends that awareness of the incidence of precocious puberty and its relationship with the self-esteem of preadolescent girls be created among parents, teachers, peers, policymakers, and other stakeholders so that the negative effects from the incidence can be mitigated.